Meta-Análise de ações e indicativos para a efetivação da Modelagem Matemática nas escolas - Foss, Ana Maria (2021)
For four decades, Mathematical Modeling has been gaining strength in the Brazilian context as an area of research and trend in Mathematics Education. Since then, Brazilian researchers have dedicated themselves to studies related to Modeling. In the context of Basic Education, researches have pointed out its timid presence in schools. From the immersion in this region of inquiry, the presence of actions and indications for the insertion of modeling in schools stood out, leading us to a research question under a phenomenological view: what do the actions and indications of the Modeling community reveal about its effectiveness in Basic Education? Guided by this question, we direct our gaze to the proceedings of the 10th National Conference on Modeling in Mathematics Education (CNMEM). One hundred texts were analyzed, including scientific communications and experience reports. These were analyzed in their entirety and read repeatedly to establish the units of meaning and convergences that culminated in open categories. From the hermeneutics undertaken, it was revealed the existence of actions carried out by the Modeling community that focus almost entirely on formations that take Modeling as the main foundation and formative principle. In addition, many of the actions and indications proved to be innocuous, since they are centered on what they deny: the transmission of content, playing a theoretical game, without considering aspects inherent to the teacher who adopts the Modeling and to the phenomenon: "Modeling in School".